Genetic Diversity of Leafy Liverwort Species (Jungermanniidae, Marchantiophyta) in Poland: Regional Genetic Differentiation of Leafy Liverworts - Bączkiewicz, Alina (Biodiversity: Research and Conservation, 2013)
For each of 8 species of leafy liverworts, 9-10 populations were sampled in 2-3 regions of Poland. In total, 5 regions were taken into account: the Tatra National Park, Bieszczady Mts., Białowieża Forest, Pomeranian Lake District, and Suwałki Lake District. Populations of most of the studied species did not show any correlation between genetic differentiation and geographic distances. Clear differences between regional groups of populations were found in only 2 species. The other species showed a complete or partial lack of genetic differentiation between groups of populations from various geographic regions. Generally, however, mountain populations had greater genetic diversity (HT, HS) and coefficient of genetic differentiation (GST) than lowland populations. In the Tatra National Park all the studied liverworts turned out to be more diverse than in the Bieszczady Mts. Białowieża Forest created a uniform group, standing out markedly from mountainous populations but population in this region had slightly smaller genetic diversity, then in the mountains. In the Pomeranian and Suwałki Lake Districts, genetic diversity of liverworts was significantly lower than in mountains. The decrease in diversity in these regions is a likely consequence of habitat fragmentation (causing population depletion) combined with negative effects of urban development. Habitat fragmentation results in genetic drift and inbreeding depression, which cause a decrease in genetic diversity. In the Pomeranian Lake District the level of total diversity (HT) and intra-population diversity (HS) was markedly higher than in the Suwałki Lake District. It may be linked to differences in climate, in the Suwałki Lake District climate is stronger.